2019
DOI: 10.1001/jamanetworkopen.2019.3442
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Major Depressive Disorder Among Women at Public Antenatal Clinics From Refugee, Conflict-Affected, and Australian-Born Backgrounds

Abstract: Key Points Question What is the prevalence and which risk factors are associated with major depressive disorder in women from conflict-affected backgrounds resettling in a high-income country, and does self-identification as a refugee signal a higher risk? Findings In this cross-sectional study of 1335 women (685 recruited from conflict-affected backgrounds and 650 from the host nation), the prevalence of major depressive disorder was 14.5% for women born i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 16 publications
2
60
0
1
Order By: Relevance
“…Nine studies mentioned the reliability or validity of the used instruments [ 23 , 35 , 36 , 39 , 41 , 44 46 , 51 ]. Thirteen studies conducted the assessment in the refugee’s native language [ 25 , 31 , 32 , 37 , 39 , 42 , 43 , 45 47 , 51 53 ]. Thirteen studies were conducted with assistance from interpreters [ 23 , 24 , 33 36 , 38 , 40 , 41 , 44 , 48 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies mentioned the reliability or validity of the used instruments [ 23 , 35 , 36 , 39 , 41 , 44 46 , 51 ]. Thirteen studies conducted the assessment in the refugee’s native language [ 25 , 31 , 32 , 37 , 39 , 42 , 43 , 45 47 , 51 53 ]. Thirteen studies were conducted with assistance from interpreters [ 23 , 24 , 33 36 , 38 , 40 , 41 , 44 , 48 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies of depression were identified ( n = 3,877) [ 23 , 25 , 33 , 35 37 , 39 45 , 49 51 , 53 ]. Participants had a weighted mean age of 35.7 years and 48% were women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They encompass, but are not limited to, female feticide, sexual abuse of girls, female genital mutilation, dowry‐related violence, sexual harassment and intimidation at work, trafficking, and violence perpetrated by an intimate partner. Women who are Indigenous or members of ethnic or religious minority groups, occupying low socio‐economic positions, or refugees or asylum‐seekers, are especially vulnerable. Experiencing or witnessing interpersonal violence, especially when it occurs within households, is always harmful to mental health.…”
mentioning
confidence: 99%